2001
DOI: 10.1128/aem.67.3.1044-1051.2001
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Populations Involved in Cycling of Dimethyl Sulfide and Methanethiol in Freshwater Sediments

Abstract: Although several microorganisms that produce and degrade methanethiol (MT) and dimethyl sulfide (DMS) have been isolated from various habitats, little is known about the numbers of these microorganisms in situ. This study reports on the identification and quantification of microorganisms involved in the cycling of MT and DMS in freshwater sediments. Sediment incubation studies revealed that the formation of MT and DMS is well balanced with their degradation. MT formation depends on the concentrations of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 41 publications
7
61
1
2
Order By: Relevance
“…16S rRNA gene sequence analysis, FISH and electron microscopy. Total genomic DNA from S. cuspidatum plants containing methanotrophs, isolated with combined methods 17 , was used as template for PCR amplification of 16S rRNA genes. PCR was performed with general bacterial primers 18 using a T gradient thermal cycler (Biometra), and a clone library was made as described previously 18 .…”
Section: Methodsmentioning
confidence: 99%
“…16S rRNA gene sequence analysis, FISH and electron microscopy. Total genomic DNA from S. cuspidatum plants containing methanotrophs, isolated with combined methods 17 , was used as template for PCR amplification of 16S rRNA genes. PCR was performed with general bacterial primers 18 using a T gradient thermal cycler (Biometra), and a clone library was made as described previously 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Release of intracellular odorants could lead to an increase of the musty odor intensity (Zamyadi et al, 2015). At the same time, the organic particles could become an important source for some reducing odorants like thioethers if sludge is not removed from the sedimentation tank in a timely fashion (Lomans et al, 1997). This process will be further discussed later.…”
Section: Mitigation Of the Septic And Musty Odorsmentioning
confidence: 99%
“…Some septic odorants such as thioethers (DMDS, DEDS, etc.) could be generated (Lomans et al, 1997), and part of the odorants adsorbed on the particles could be dissolved into water during the anaerobic digestion. Thus this study demonstrated that the release of odorants could take place under normal operational conditions.…”
Section: Odorant Removal In Wtpmentioning
confidence: 99%
“…The main source of DMS is considered to be the enzymatic cleavage of dimethylsulfonium propionate (DMSP) from phytoplankton and macroalgae in marine environments (Aneja and Overton 1990). DMDS also could result from the decomposition of sulfur-containing organic compounds (Lomans et al 1997). In addition, MT can be oxidized easily to form DMDS in the presence of an oxidant (e.g., oxygen) (Adewuyi 1989).…”
Section: The Temporal Variability Of Emissions Of Voscs From Shijing mentioning
confidence: 99%